Photocatalytic splitting of CS2 to a carbon-sulfur polymer and S8 catalyzed by a bimetallic ruthenium(II) compound with a tertiary amine binding site - towards photocatalytic splitting of CO2? - Livanov, Konstantin; Madhu, Vedichi; Balaraman, Ekambaram; Shimon, Linda J. W.; Diskin-Posner, Yael; Neumann, Ronny (Inorganic Chemistry, 2011)
The catalytic photocleavage of CS2 to S8 and a (CxSy)n polymer with visible light using a dinuclear ruthenium(II) compound with a bipyridine units for photoactivity and a vicinal tertiary amine binding site for CS2 activation was studied. The catalyst was characterized by X-ray diffraction, 1H NMR, and 13C NMR, ESI-MS and elemental analysis. CS2 photocleavage was significant (240 turnovers, 20 h) to yield isolable S8 and a (CxSy)n polymer. A mononuclear catalyst or one without an amine binding site showed significantly less activity. XPS of the (CxSy)n polymer showed a carbon/sulfur ratio ∼1.5–1.6 indicating that in part both C–S bonds of CS2 had been cleaved. Catalyst was also included within the polymer. The absence of peaks in the 1H NMR verified the (CxSy)n nature of the polymer, while 13C NMR and IR indicated that the polymer had multiple types of C–S and C–C bonds.

PNN-Ru pincer complexes based on phosphinated 2,2’-dipyridinemethane- and 2,2’-oxobispyridine. metal-ligand cooperation in cyclometallation and catalysis - Barrios-Francisco, Rigoberto; Balaraman, Ekambaram; Diskin-Posner, Yael; Leitus, Gregory; Shimon, Linda J. W.; Milstein, David (Organometallics, 2013)
The synthesis of novel PNN ruthenium pincer complexes based on 2,2′-dipyridinemethane phosphine derivatives, as well as on 2,2′-oxobispyridine phosphine ligands, and their reactivity toward dearomatization and cyclometalation are described. The dearomatized compounds 7a,b undergo cyclometalation to yield complexes 8a,b. In order for cyclometalation to proceed, the coordination sphere around the Ru center has to rearrange, and this depends on the flexibility of the system, showing that the cyclometalation is qualitatively faster in the case of the dimethyl derivative 7a than in the case of the spyrocyclopentyl derivative 7b. The cyclometalation occurs diastereoselectively and leads to only one diastereomer of the cyclometalated compounds. In the case of the 2,2′-oxobispyridine complex 6c, the dearomatized complex was too unstable to be isolated; however it was possible to isolate and characterize a stable dicarbonyl-dearomatized ruthenium(II) complex, 9c, when the deprotonation was performed under a CO atmosphere. Dearomatization of 6a under CO also led to dicarbonyl-dearomatized ruthenium(II) complex 9a, which slowly rearranged into the dicarbonyl-aromatized ruthenium(0) complex 10a. These complexes were tested in catalytic alcohol–amine coupling, esterification of primary alcohols, and hydrogenation of secondary amides. Moderate activity was observed in hydrogenation of amides to alcohols and amines and low activity in the other transformations, owing mainly to the formation of stable cyclometalated compounds.